Learning to learn - Doğan, Yunus; Tamur, Sabiha; Batdi, Veli (Nova Science Publishers, Inc., 2024)
Constantly evolving technological advancements, changing societal needs, and the necessity for individuals to fully and continuously engage in evolving job fields and society have made the skill of learning to learn a compulsory requirement. The Future of Higher Education Report indicates that recent university graduates entering the workforce are not yet competent or prepared for their work environments, lacking the critical thinking and problem-solving skills essential in today's job market. Learning is a skill that should not only be confined to the university education process but should continue throughout life. This skill has been under scrutiny by scientists since the late 20th century. In the year 2000, the Lisbon European Council acknowledged the difficulties in adapting to the globalization of the economy and the knowledge-based changes, identifying the need to develop individuals capable of coping with these changes. As learning how to learn forms the foundation for lifelong learning, it is essential to create a learning environment within educational settings for all members of society to develop this skill. This study examines research conducted on the subject of learning how to learn. Information was gathered by scanning the databases of Google Scholar, Taylor and Francis, Scopus, and Web of Science. The literature review revealed that the studies obtained aimed to understand the characteristics of the skill of learning how to learn, how it can be imparted, assessed, and incorporated into educational programs. This study delves into defining the skill of learning how to learn, its characteristics, significance, evaluation, the roles of schools and other educational stakeholders in the process of enhancing this skill, and its place in education systems of other countries. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Assessment of learning to learn skill; Learning; Learning to learn